2018
DOI: 10.1007/s00296-018-4022-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum drug levels of biologic agents in the management of rheumatoid arthritis and spondyloarthritis: a systematic review

Abstract: The utility of monitoring drug levels in rheumatoid arthritis and spondyloarthritis patients on biological therapy is called into question. The objective was to study relevant clinical questions on the topic, i.e., (1) whether drug levels predict relapse in patients whose biologic was optimized because of remission or low disease activity; (2) whether information about drug levels influences the prognosis of patients with primary or secondary failure to a biological therapy; and (3) whether methotrexate (MTX) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Because many currently available drugs induce side effects, patient compliance is very poor. Although the use of biological agents for RA has increased in recent years, it is expensive, and this has greatly limited the application of biological agents for RA 1821. In the USA, the annual direct medical cost of each patient is about $13,500, and the indirect cost is between $1,000 and $33,000 22…”
Section: Discussionmentioning
confidence: 99%
“…Because many currently available drugs induce side effects, patient compliance is very poor. Although the use of biological agents for RA has increased in recent years, it is expensive, and this has greatly limited the application of biological agents for RA 1821. In the USA, the annual direct medical cost of each patient is about $13,500, and the indirect cost is between $1,000 and $33,000 22…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the use of infliximab presents the higher potential of immunogenicity, with the development of antidrug antibodies (ADA), as compared with the remaining anti-TNF agents. The anti-drug antibodies (ADA) are associated with decrease of clinical response and increasing incidence of reactions to infusion as well as to reactions at the application site [22,23]. Besides this, lower adhesion to treatment with infliximab has been demonstrated in other immunomediated diseases when compared with other anti-TNF agents [24], which could be explained by its higher potential for adverse reactions, mainly infusional ones and in the application site, and by its administration path [18,[22][23][24]; patients with rheumatic diseases might present preference for subcutaneous administration instead of intravenously and for home administration instead of hospital [24].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-drug antibodies (ADA) are associated with decrease of clinical response and increasing incidence of reactions to infusion as well as to reactions at the application site [22,23]. Besides this, lower adhesion to treatment with infliximab has been demonstrated in other immunomediated diseases when compared with other anti-TNF agents [24], which could be explained by its higher potential for adverse reactions, mainly infusional ones and in the application site, and by its administration path [18,[22][23][24]; patients with rheumatic diseases might present preference for subcutaneous administration instead of intravenously and for home administration instead of hospital [24]. However, this result should be interpreted with caution as infliximab has shown better persistence in particular subsets, such as in oligoarticular-PsA [26].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent study by Pedersen et al who showed that therapeutic drug monitoring of TNF inhibitors leads to better clinical response and cost management in the treatment of patients with rheumatic diseases [ 52 ]. A recent review concluded that measuring drug levels and ADAb in RA and SpA patients with biologic treatment might be useful both in case of poor response and longer clinical remission [ 53 ].…”
Section: Discussionmentioning
confidence: 99%